RELIGIOUS EDUCATION IN SCHOOLS: A GAP BETWEEN HOPE AND REALITY AND THE SOLUTION - Nengah Bawa Atmadja (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2023)
This article results from a literature study that describes the discrepancy between expectations and reality in religious education in schools and the solution. The purpose of this research is not only to explain the weaknesses of religious education in schools, reflected in the gap between expectations and reality, but also to provide a solution. This research was conducted by critically reviewing various books. The data obtained is synthesized by following the line of thought of critical social theory. The study results show that the gap between expectations and reality in religious education in schools is mainly due to the pattern which emphasizes exclusivism more than inclusivism. This condition requires revitalization through the implementation of inclusive and interreligious religious education. Its application adheres to the characteristics of inclusivism combined with the ethical wisdom of the Bhagawad Gita. This is complemented by the intertwined development of habits of thought, speech, social action, and morality so that a wise acceptance of religious diversity emerges. An inclusive religious education method requires a learning method of habituation, modeling, normalizing, and disciplining the student body. Applying this method requires the cooperation of various teachers, especially teachers in schools and parents of students.